Survey Study of Student Perceptions of Prospective Chemistry Teachers on the Development of Small-Scale Chemistry Practicums - Mubarokah, Febriati Dian; Hana, Muhammad Nurul (Universitas Pendidikan Mandalika, 2025)
The small-scale chemistry laboratory approach remains relatively unfamiliar and underutilized by chemistry teachers in Indonesia. This is largely due to the gap between theoretical understanding and the practical skills required to design laboratory activities that are not only environmentally friendly but also aligned with learning objectives. This study aims to examine the perceptions of pre-service chemistry teachers regarding the development of small-scale chemistry practicums and their impact on motivation to learn and implement them at school. The novelty of this research lies in the participatory involvement of pre-service teachers, who are engaged not only as participants but also as designers of the practicum procedures, thereby providing authentic experiences in their professional preparation as future teachers. Employing a qualitative approach with a survey method, the study involved 26 first-year students from the Chemistry Education Program enrolled in the School Chemistry Practicum course. Data were collected through questionnaires, students’ practicum reports, and classroom observations. The findings indicate that student perceptions of the development and implementation of small-scale chemistry practicum were generally in the